Reimagining To kill a mockingbird : family, community, and the possibility of equal justice under law - Umphrey, Martha Merrill; Sarat, Austin (Amherst : University of Massachusetts Press, 2013)
Fifty years after the release of the film version of Harper Lee's acclaimed novel To Kill a Mockingbird, this collection of original essays takes a fresh look at a classic text in legal scholarship. The contributors revisit and examine Atticus, Scout, and Jem Finch, their community, and the events that occur there through the interdisciplinary lens of law and humanities scholarship. The readings in this volume peel back the film's visual representation of the many-layered social world of Maycomb, Alabama, offering sometimes counterintuitive insights through the prism of a number of provocative contemporary theoretical and interpretive questions. What, they ask, is the relationship between the subversion of social norms and the doing of justice or injustice? Through what narrative and visual devices are some social hierarchies destabilized while others remain hegemonic? How should we understand the sacrifices characters make in the name of justice, and comprehend their failures in achieving it? Asking such questions casts light on the film's eccentricities and internal contradictions and suggests the possibility of new interpretations of a culturally iconic text. The book examines the context that gave meaning to the film's representation of race and how debates about family, community, and race are played out and reframed in law.
A Reimagining To Kill a Mockingbird: An Introduction / MARTHA MERRILL UMPHREY & AUSTIN SARAT -- Temporal Horizons: On the Possibilities of Law and Fatherhood in To Kill a Mockingbird / AUSTIN SARAT & MARTHA MERRILL UMPHREY -- I Would Kill for You: Love, Law, and Sacrifice in To Kill a Mockingbird / LINDA ROSS MEYER -- Motherless Children Have a Hard Time: Man as Mother in To Kill a Mockingbird / THOMAS L. DUMM -- If That Mockingbird Don't Sing: Scaffolding, Signifying, and Queering a Classic / IMANI PERRY -- A Ritual of Redemption: Reimagining Community in To Kill a Mockingbird / NAOMI MEZEY -- "We Don't Have Mockingbirds in Britain, Do We?" / SUSAN SAGE HEINZELMAN -- Dead Animals / RAVIT REICHMAN -- Humans, Animals, and Boundary Objects in Maycomb / COLIN DAYAN.
Includes bibliographical references (pages 185-187) and index.
Print version record.
JSTOR
Keywords: Lee, Harper; Lee, Harper; To kill a mockingbird (Lee, Harper); Law in literature; Droit dans la littérature.; SOCIAL SCIENCE -- General; Law in literature